تحليل بيئة اللغة العربية في معهد التبيان بدلي سردانج في ضوء الكفاية التواصلية: دراسة نوعية - Mhd Firdaus Lubis (Arabiyyatī: Journal of Arabic Language Education, 2025)
Abstract This study analyzes the Arabic language environment at Al-Tibyan Institute in Deli Serdang from the perspective of communicative competence, viewing it as an integrated institutional system linking lang uage policies, curricular and extracurricular activities, disciplinary and motivational mechanisms, and daily student practices. Using a qualitative descriptive-analytical approach, data were collected through direct observation, in-depth interviews, and document analysis. Results show the environment features institutional discipline, intensive language exposure, and integration of activities, enhancing speaking, listening, writing, and social interaction skills. Supporting factors include committed administration and teachers, organized programs, and effective educational practices. Inhibiting factors involve limited free interaction beyond formal settings, mother tongue influence, and lack of some resources. This study offers a practical model to activate the Arabic language environment, promoting functional and social communicative competence in religious institutions and supporting continuous educational quality and development for students and teachers. Keywords: Arabic language environment, communicative competence, institutional policies, educational practices